Fundamental challenges in designing a collaborative travel app. (November 2015) - Dickinson, Janet E.; Cherrett, Tom; Hibbert, Julia F.; Winstanley, Chris; Shingleton, Duncan; Davies, Nigel; Norgate, Sarah; Speed, Chris
Abstract: The growing capabilities of smartphones have opened up new opportunities for travel coordination and transport is a fertile area for app development. One stream of development is apps that enable collaborative travel, either in the form of lift sharing or collaborative shopping, but despite growing interest from governmental agencies, there is little evidence of the efficacy of such apps. Based on trials of purpose built travel collaboration apps, deployed in tourism, urban and rural residential communities, and logistics, this paper analyses the fundamental challenges facing users adopting such travel apps. The findings suggest that transport practitioners, policy makers and app developers need to better understand the challenges associated with attracting users, the use of incentives and the types of communities most appropriate to implement collaborative travel concepts using such approaches. Also, how the users' sense of time pressure and the issues around reciprocal exchange can impact on their long-term success and wider adoption. Highlights: Designing and implementing collaborative travel enabled by a smartphone app. Challenges of attracting users and use of incentives in collaborative travel apps. The barriers of reciprocal exchange in collaborative travel. Selecting appropriate of communities to implement collaborative travel concepts.